Re-writing Pasts, Imagining Futures : Critical Explorations of Contemporary African Fiction and Theater - Ndi, Gilbert Shang, 1982-; Gomia, Victor N. (Book collections on Project MUSE., 2018)
This book is a collection of essays on various aspects of contemporary African fiction and theater. The breadth and depth of the collection speak to the innovative trends in African fiction and theater in an increasingly interconnected world. Whereas the views of the authors are inherently diverse, common grounds are gleaned in the commonality of the patterns of artistic visions shaped and given impetus by the peoples' new world realities; in this sense, the essays are at the same time in dialogue with each other. In the context of colonial and neo-colonial legacies that seem to forestall any sense of individual and collective self-fulfillment, contributors to this volume examine the pertinence of African fiction and theatre in imagining new vistas of re-conceptualizing the postcolonial condition in ways that re-galvanize the belief in an enabling future.